The Visuality of the Funerary Discourse - Hassan Jamel Hassan, Dr. (lark, 2026)
This study investigates the visual rhetoric embedded in the funeral discourse surrounding the procession of the “Master of the South,” viewing it as a dense discursive event where religious, political, and cultural symbols converge within a resistant narrative framework. The research is grounded in the premise that the visual sign is no longer a decorative or secondary element, but rather a central semiotic unit performing powerful communicative and affective functions, shaping a discourse that transcends mourning into a mobilizing field rooted in the rhetoric of emotions and the semiotics of identity. The study demonstrates how the funeral transformed into a multidimensional communicative system by employing the recorded voice of the deceased leader, images of his coffin, the symbolic black turban, and slogans such as the pledge, which collectively formed a popular discourse laden with interpretive potential and metaphorical density, It further highlights the role of both spontaneous and orchestrated public engagement in producing what may be termed discursive clusters, blending textual, visual, and symbolic elements to create a resistant discourse with transnational resonance. The analysis traces these visual signs within their broader political and cultural contexts, revealing the rhetorical strategies employed by both sides—resistance movements and the Zionist entity—in a symbolic battle for narrative and influence. The study concludes that the visual funeral rhetoric of resistance has evolved beyond memorialization, becoming a deliberate strategy for reinforcing collective identity, activating historical memory, and affirming the principles of defiance through an intentional and effective deployment of modern expressive tools in a confrontational discourse.